Experimental study on stainless steel tubular members under cyclic loading. (December 2022) - González-de-León, Isabel; Nastri, Elide; Arrayago, Itsaso; Montuori, Rosario; Piluso, Vincenzo; Real, Esther
Abstract: Stainless steel is an excellent construction material due to its high ductility, strain hardening, durability and aesthetic characteristics. To date, most studies on stainless steel have been devoted to understanding its mechanical properties and the behaviour of individual structural members and simple structures under monotonic loading. As a result, next versions of stainless steel codes, traditionally based on carbon steel codes, will enable efficient structural designs under static forces. However, advances related to the performance of stainless steel structural members under cyclic forces are still scarce, and there are no specific rules for the seismic design of stainless steel structures in Eurocode 8 in spite of the notable differences between this material and other steels. On this basis, an experimental programme on austenitic stainless steel hollow section elements subjected to cyclic loading has been recently conducted. A total of nine specimens with different local and member slenderness values were tested under cyclic bending around their major axis following a cantilever loading scheme. This paper describes the experimental set-up adopted for the tests, including the loading scheme and instrumentation, and discusses the load–displacement, moment–rotation, degradation of stiffness and energy dissipation values obtained in detail. In addition to providing fundamental information on the response of stainless steel members under cyclic loading, the description of the set-up reported in this paper will assist researchers in planning similar experimental programmes, while the results will serve as a reference to validate numerical analyses of stainless steel members and frames subjected to cyclic loading. Highlights: Austenitic stainless steel hollow section members are tested under cyclic bending. Specimens with different local and member slenderness values are covered. The adopted experimental set-up and loading protocol are defined. The resulting load–displacement and moment–rotation responses are provided. The stiffness degradations and energy dissipation capabilities are discussed.